THE EFFECT OF PLANT SPACING AND CHICKEN MANURE ON GROWTH AND RESULT OF RICE PLANTS USING THE SRI METHOD ON TIDAL LAND - Ema Ema; Mulyadi Safwan; Maulidi Maulidi (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the effect of plant spacing and chicken manure on the growth and yield of rice plants by using the SRI method on tidal land and their interactions. The study was carried out in Kalimas Village, Sungai Kakap District, Kubu Raya District, on tidal land. This research was conducted from November 2017 - March 2018, using a divided plot design consisting of spacing of 20 cm x 20 cm, 30 cm x 30 cm, and 40 cm x 40 cm as sub plot and chickens manure 5 tons/ha and 10 tons/ha as main plot. Each treatment was repeated 4 times, with 5 sample plants per map. The observation variables in this study were plant height, maximum number of tillers, number of productive tillers, panicle length, total grain per panicle, percentage of filled grain per panicle, weight of 1000 grain items, weight of grain per clump and weight of grain per plot. The results showed that the treatment of spacing had a significant effect on the variable number of maximum tillers, number of productive tillers, total grain count per panicle, weight of 1000 grains and weight of grains per clump. The results of the analysis of the diversity of doses of chicken manure significantly affected plant height, number of tillers, number of productive tillers, weight of grain per grain and weight of paddy grain. Interactions between treatments only significantly affect the number of productive tillers. Effective spacing is found at a spacing of 40 cm x 40 cm, and the best dose of chicken manure is at a dose of 10 tons/ha. Interactions occur in observing the number of productive tillers, namely the best combination at a spacing of 40 cm x 40 cm and the provision of 10 tons/ha of chickens manure.Keywords : rice, spacing , chicken manure, situ bagendit variety, SRI method.